NECROSIS OF THE OMENTAL PROCESS OF THE DESCENDING COLON, SIMULATED AN ACUTE ABDOMEN (CASE REPORT) - Baimakov, S.R.; Ashirmetov, A.Kh.; Yunusov, S.Sh.; Boltaev, Sh.Sh.; Fayzullakhonov, Sh.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
In the surgical literature, the inversion of fatty suspensions of the colon was first described in 1928 by A.M. Grigoryev. Demonstrated a case of necrosis adipose pendant of descending colon. Clinical picture was simulated acute abdomen, for differential diagnosis videolaparoscopy was used, which was allowed to correcting diagnose and successfuly execute laparoscopic operation for ablate the necrotizing appendix of epiploon.